2013
DOI: 10.1007/s00590-013-1292-0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed surgery in displaced paediatric supracondylar fractures: a safe approach? Results from a large UK tertiary paediatric trauma centre

Abstract: Our results indicate that delayed surgery appears to offer a safe management approach in the treatment of displaced supracondylar fractures, but it is important that cases are carefully evaluated on an individual basis. These results indicate that patient transfer to a specialist paediatric centre, often with consequent surgical delay, is a safe management option and also negates the obligation to carry out these procedures at night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
4
16
0
Order By: Relevance
“…This is much higher than the 3.9 % for iatrogenic neurapraxia after closed reduction and percutaneous pinning from a recent meta-analysis [2]. Unfortunately, Mayne et al [1] do not provide a figure for the traumatic preoperative nerve injury rate. These data are important, not only because adverse neurology might influence the timing of surgery (and therefore affect case allocation to the 'early' or 'delayed' group), but also in that, it might account (in part) for the large post-operative nerve injury rate.…”
Section: Dear Editormentioning
confidence: 88%
See 1 more Smart Citation
“…This is much higher than the 3.9 % for iatrogenic neurapraxia after closed reduction and percutaneous pinning from a recent meta-analysis [2]. Unfortunately, Mayne et al [1] do not provide a figure for the traumatic preoperative nerve injury rate. These data are important, not only because adverse neurology might influence the timing of surgery (and therefore affect case allocation to the 'early' or 'delayed' group), but also in that, it might account (in part) for the large post-operative nerve injury rate.…”
Section: Dear Editormentioning
confidence: 88%
“…I was interested to read the article 'Delayed surgery in displaced paediatric supracondylar fractures: a safe approach? Results from a large UK tertiary paediatric trauma centre' by Mayne et al [1]. This study purports to show that 'delayed surgery appears to offer a safe management approach to the treatment of displaced supracondylar fractures', in part because of the lack of significant differences in complication rates between those operated on before and after 12 h.…”
Section: Dear Editormentioning
confidence: 99%
“…The most common fracture operatively treated at this institution is the supracondylar humerus fracture. To date several studies have been published on the outcomes of these fractures after surgical delay [12][13][14][15][16] . All of the studies reviewed found no increase in the complication rate, which has further allowed surgeons to address these injuries in a more delayed fashion.…”
Section: Discussionmentioning
confidence: 99%
“…There were no further exclusions. Our state has instituted a trauma policy that all children younger than 16 Simple means were calculated utilizing Microsoft Excel 2010. χ 2 testing was performed to compare variables among the three groups. Statistical analysis was conducted using SAS 9.2 (SAS, Cary, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We recognise that both of these factors are a cause for concern and that high iatrogenic injury may be erroneously attributed as a result of poor recognition of pre-operative nerve injury. The 'test' of neurological documentation was set deliberately high in the original paper investigating neurovascular documentation [1]-that is, we required documentation of individual nerves in terms of sensory and motor function, such as is required for medicolegal purposes. The reality is that most pre-operative documentation was probably of similar quality to other units (i.e.…”
Section: Dear Editormentioning
confidence: 99%